O Colégio Seráfico de Santo Antônio e suas práticas escolares (1941-1971) - Santos, José Roberto Morais dos (2017)
The present dissertation intends to analyze the school practices that took place in the Seraphic College of Santo Antônio, in Lagoa Seca-PB, from 1941 to 1971. In this perspective, the contribution of the New Cultural History made possible the development of this research, with a new investigative look about subjects who were once reneged on by Traditional History. The methodology of this study uses oral history and memory as historiographic sources allied to imagery sources. The contribution of these subjects was made through their memories, considering that these subjects did not keep letters, diaries, notebooks, among others. In this way, it is understood that there is no way to study school practices without tracing the trajectory in which these relations take place. In analyzing these school practices, we notice a little more about the history of education in that municipality and the contributions that these practices have brought. The temporal cut used allows to understand and to know a little more of the history of the CSSA. With regard to the concepts that underpinned this dissertation, we highlight: discussions about the cultural history of Burke (2005); the role of the church in men's school education in the 1950s by Chaves (2012); culture and school practices from Vidal's perspective (2006); and the new approaches of the field of the history of the Brazilian education of Ricouer (2007). As for the thematic discussion about the school institution, the approaches of Faria Filho (1995) and Halbawachs (2004) were pertinent. Among the various reflections developed in this study, we could conclude that the CSSA was a religious education, preparing students for ecclesiastical formation, but not all the students became friars, and other formations as lawyers, university professors, and several other professions practiced in the north - northeast of Brazil, through a curriculum and school practices that emphasized a religious formation.